Frequency of pancreatitis in fulminant hepatic failure using isoenzyme markers. - Ede, R J (1988)
Evidence of acute pancreatitis was sought in 35 patients with fulminant hepatic failure. Total amylase was raised in 22 patients and isoenzyme separation showed a distinct P3 isoenzyme (indicative of pancreatitis) in 14. In four patients with marked hyperamylasaemia (greater than 1000 U/l) the predominant isoenzyme was the salivary fraction. Pancreatic lipase was abnormally raised (greater than 200 U/l) in 34 patients but exceeded 1000 U/l in 12 of the 14 with a distinct P3 isoenzyme. Thus on the basis of a distinct P3 isoenzyme of amylase and an increased pancreatic lipase activity evidence of pancreatitis was found in 34% of patients in this series.